Experimental vaccination by single dose sporozoite injection of blood-stage attenuated malaria parasites - Sattler, Julia M.; Keiber, Lukas; Abdelrahim, Aiman Gamal; Zheng, Xinyu; Jäcklin, Martin; Zechel, Luisa; Moreau, Catherine; Steinbrück, Smilla; Fischer, Manuel; Janse, Christoffel J.; Hoffmann, Angelika; Hentzschel, Franziska; et al. (EMBO molecular medicine, 2024)
Malaria vaccination approaches using live Plasmodium parasites are currently explored, with either attenuated mosquito-derived sporozoites or attenuated blood-stage parasites. Both approaches would profit from the availability of attenuated and avirulent parasites with a reduced blood-stage multiplication rate. Here we screened gene-deletion mutants of the rodent parasite P. berghei and the human parasite P. falciparum for slow growth. Furthermore, we tested the P. berghei mutants for avirulence and resolving blood-stage infections, while preserving sporozoite formation and liver infection. Targeting 51 genes yielded 18 P. berghei gene-deletion mutants with several mutants causing mild infections. Infections with the two most attenuated mutants either by blood stages or by sporozoites were cleared by the immune response. Immunization of mice led to protection from disease after challenge with wild-type sporozoites. Two of six generated P. falciparum gene-deletion mutants showed a slow growth rate. Slow-growing, avirulent P. falciparum mutants will constitute valuable tools to inform on the induction of immune responses and will aid in developing new as well as safeguarding existing attenuated parasite vaccines.